2021
DOI: 10.1111/apt.16714
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review with meta‐analysis: the effectiveness of either ustekinumab or vedolizumab in patients with Crohn's disease refractory to anti‐tumour necrosis factor

Abstract: Summary Background Ustekinumab and vedolizumab are commonly used after anti‐tumour necrosis factor (TNF) failure in patients with Crohn’s disease (CD). No randomised controlled trial has compared these drugs. Aims To compare the effectiveness of ustekinumab and vedolizumab in CD patients refractory to anti‐TNF. Methods From PubMed, EMBASE and the Cochrane Library, through March 27, 2021, we identified studies that compared ustekinumab and vedolizumab in patients with CD refractory to anti‐TNF. The main outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 32 publications
(61 reference statements)
2
22
0
Order By: Relevance
“…No differences were reported at week 24, whereas at week 52, a small but significant difference (∆ 10%) was found in favor of UST. A recent meta-analysis including the aforementioned studies favored UST over VDZ in the induction of SFR at week 52 but not at week 14 (15).…”
Section: Discussionmentioning
confidence: 99%
“…No differences were reported at week 24, whereas at week 52, a small but significant difference (∆ 10%) was found in favor of UST. A recent meta-analysis including the aforementioned studies favored UST over VDZ in the induction of SFR at week 52 but not at week 14 (15).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, prospective registry data and retrospective observational data have shown that in individuals with CD are more likely to achieve and remain in remission on UST, 16 , 17 and a recent meta-analysis shows that UST is more effective than VDZ for maintenance in people with anti-TNF-refractory CD. 18 …”
Section: Discussionmentioning
confidence: 99%
“… 25 A meta-analysis that compared the efficacies of UST and VDZ in CD also collected data about clinical SFR and treatment persistence and found significant superiority of UST in both clinical SFR at week 52 and in drug persistence. 26 A recent multicentre-retrospective study from Italy displayed the equality of UST and VDZ in terms of achieving objective remission among patients with anti-TNF refractory CD at week 52; however, clinical remission rates differed. 27 Our study found 1-year persistence rates of 86.5% for UST and 57.9% for VDZ treatment, which are higher than the rates found by Ylisaukko-Oja et al of 46.2%–37.1% for ADA and 47.1% for UST during 12 months of treatment in a real-life setting.…”
Section: Discussionmentioning
confidence: 99%